2011
DOI: 10.1111/j.1538-7836.2011.04451.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of miRNAs as potential modulators of tissue factor expression in patients with systemic lupus erythematosus and antiphospholipid syndrome

Abstract: To cite this article: Teruel R, Pé rez-Sá nchez C, Corral J, Herranz MT, Pé rez-Andreu V, Saiz E, García-Barberá N, Martínez-Martínez I, Roldá n V, Vicente V, Ló pez-Pedrera C, Martínez C. Identification of miRNAs as potential modulators of tissue factor expression in patients with systemic lupus erythematosus and antiphospholipid syndrome. J Thromb Haemost 2011; 9: 1985-92.Summary. Background: Tissue factor (TF) is the main initiator of the coagulation cascade and elements that may upregulate its expression m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
73
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(77 citation statements)
references
References 40 publications
0
73
0
4
Order By: Relevance
“…27 The stability of TF mRNA is known to be regulated by miR 19a/19b and by miR201/20b/106b, acting at distinct binding sites proximal to the conserved ARE engaged by the interaction of PARP-14 and TTP. [31][32][33] Using a luciferase mRNA stability reporter assay, we found that the 2 miR sites and the conserved ARE each contribute to reducing reporter activity in the assay, and have additive effects in combination. Clearly more work is now warranted to understand the molecular interactions between ARE-mediated and miR-mediated regulation of mRNA stability in this model, both under basal conditions and dynamically after LPS or cytokine activation.…”
Section: Org Frommentioning
confidence: 99%
See 1 more Smart Citation
“…27 The stability of TF mRNA is known to be regulated by miR 19a/19b and by miR201/20b/106b, acting at distinct binding sites proximal to the conserved ARE engaged by the interaction of PARP-14 and TTP. [31][32][33] Using a luciferase mRNA stability reporter assay, we found that the 2 miR sites and the conserved ARE each contribute to reducing reporter activity in the assay, and have additive effects in combination. Clearly more work is now warranted to understand the molecular interactions between ARE-mediated and miR-mediated regulation of mRNA stability in this model, both under basal conditions and dynamically after LPS or cytokine activation.…”
Section: Org Frommentioning
confidence: 99%
“…[31][32][33] To examine the relative impact of the conserved 17-nucleotide AREs compared with the miR-A and miR-B sites, we established a luciferase mRNA stability reporter assay in RAW 264.7 cells. These are of mouse macrophage origin and are known to express hypophosphorylated TTP basally without stimulation 34 and to express PARP-14 (supplemental Figure 8).…”
Section: Both Anti-ttp and Parp-14 Antibodies Immunoprecipitate Tf Mrnamentioning
confidence: 99%
“…For example, up to 40 % of SLE patients are persistently positive for aPL, even at high titre; however, less than one third of them actually display the clinical events. A similar group of aPL-positive asymptomatic carriers can also be found in subjects with no any underlying autoimmune disease and followed for a long period of time [74].…”
Section: Can Epigenetic Mechanisms Explain the Onset Of Tissue Damage?mentioning
confidence: 98%
“…Preliminary studies have shown that several members of the miR 17-92 cluster (miR-20a and miR-19b) regulate the expression of TF in monocytes from patients with APS and systemic lupus erythematosus (SLE) [27]. A reduction in their expression has been found to significantly correlate with the over-activation of TF.…”
Section: Genomic and Epigeneticmentioning
confidence: 99%
“…A reduction in their expression has been found to significantly correlate with the over-activation of TF. The reduction in the expression of these miRNAs could therefore contribute to the prothrombotic state characteristic of APS and SLE patients [27]. Data gathered in recent years explored the relationship between three groups of antiphospholipid antibodies, not currently included in the classification criteria and the development of thrombotic events.…”
Section: Genomic and Epigeneticmentioning
confidence: 99%